The contribution of shelter from rain to the success of pit-building predators in urban habitats. (August 2018) - Scharf, Inon; Gilad, Tomer; Bar-Ziv, Michael A.; Katz, Noa; Gregorian, Elena; Pruitt, Jonathan N.; Subach, Aziz
Abstract : Trap-building predators are sit-and-wait predators that construct a trap and wait for other arthropods to be captured in their trap. The abiotic features of their microhabitat play a significant role in their foraging success, and trap relocation can be costly and risky. Wormlions are fly larvae that construct pits in loose soil to catch prey that fall into their pit-traps and serve as a fine example of a trap-building predator. Wormlions flourish in cities and often occur under buildings that provide shelter from direct sunlight and rain. Here, we studied in the laboratory and in the field the effect of simulated rain and soil moisture on wormlion ( Vermileo sp.) habitat choice, response to prey and prey escape success. Wet soil had a strong negative effect on the wormlion pit size and its response to prey, and a positive effect on the probability of ant prey escaping the pit-trap. All these limitations led to a strong avoidance by wormlions of wet soil both before and after a pit was constructed, even at the cost of pit relocation. A field experiment comparing wet and dry plots nevertheless failed to show the expected directional relocation from wet to dry plots, and we provide several explanations as to why the patterns detected in the laboratory were less clear in the field. We suggest that rain presents a considerable limiting factor for wormlion hunting success, and that rain-shielding artificial structures could be responsible for the success of these predators in urban environments. It remains to be tested whether our results hold true for other trap-building predators and whether their preference for dry habitats is as strong as that of wormlions. Highlights: Pit-building predators construct pits in loose soil to capture arthropods. We tested the effect of rain on their performance and habitat choice. Rain impairs prey capture success, enabling faster escape of prey from the pit. Wet microhabitats are not favoured by pit-building predators.